Folate Intake and Markers of Folate Status in Women of Reproductive Age, Pregnant and Lactating Women: A Meta-Analysis - Cristiana Berti; Katalin Fekete; Carla Dullemeijer; Monica Trovato; Olga W. Souverein; Adriënne Cavelaars; Rosalie Dhonukshe-Rutten; Maddalena Massari; Tamás Decsi; Pieter van't Veer; Irene Cetin (Journal of Nutrition and Metabolism)
Background. Pregnant and breastfeeding women are at risk for folate deficiency. Folate supplementation has been shown to be associated with enhanced markers of folate status. However, dose-response analyses for adult women are still lacking. Objective. To assess the dose-response relationship between total folate intake (folic acid plus dietary folate) and markers of folate status (plasma/serum folate, red blood cell folate, and plasma homocysteine); to evaluate potential differences between women in childbearing age, pregnant and lactating women. Methods. Electronic literature searches were carried out on three databases until February 2010. The overall pooled regression coefficient (β) and SE(β) were calculated using meta-analysis on a double-log scale. Results. The majority of data was based on nonpregnant, nonlactating women in childbearingage. The pooled estimate of the relationship between folate intake and serum/plasma folate was 0.56 (95% CI = 0.40–0.72, P<0.00001); that is, the doubling of folate intake increases the folate level in serum/plasma by 47%. For red blood cell folate, the pooled-effect estimate was 0.30 (95% CI = 0.22–0.38, P<0.00001), that is, +23% for doubling intake. For plasma-homocysteine it was –0.10 (95% = –0.17 to –0.04, P=0.001), that is, –7% for doubling the intake. Associations tended to be weaker in pregnant and lactating women. Conclusion. Significant relationships between folate intake and serum/plasma folate, red blood cell folate, and plasma homocysteine were quantified. This dose-response methodology may be applied for setting requirements for women in childbearing age, as well as for pregnant and lactating women.